2017
DOI: 10.1007/s10695-017-0429-1
|View full text |Cite
|
Sign up to set email alerts
|

Some immunological responses of common carp (Cyprinus carpio) fingerling to acute extremely low-frequency electromagnetic fields (50 Hz)

Abstract: Increasing of anthropogenic electromagnetic fields in aquatic environments has been recently become the core of attention. In this study, the effect of extremely low-frequency electromagnetic fields (50 Hz) on immune status and metabolic markers of common carp fingerling was assessed. The fish were exposed to extremely low-frequency electromagnetic fields at four intensities of 0.1, 0.5, 1, and 2 mT only once for 2 h; then, they were reared for 60 days. Results showed that the levels of aspartate aminotransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Similar phenomena have been reported in many aquatic organisms previously. For example, studies showed that, the lysozyme level significantly decreased, and the AST and ALT levels significantly increased upon magnetic field exposure in Cyprinus Carpio ( Khoshroo et al, 2018 ) and Caspian kutum ( Loghmannia et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar phenomena have been reported in many aquatic organisms previously. For example, studies showed that, the lysozyme level significantly decreased, and the AST and ALT levels significantly increased upon magnetic field exposure in Cyprinus Carpio ( Khoshroo et al, 2018 ) and Caspian kutum ( Loghmannia et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because IMF-MFs is 300 Hz through 100KHz or10 MHz [2]; [64] ELF-MFs is 0Hz through 300Hz and the author thinks ELF-MFs may be regarded as static and corresponding effects can be explained through Equation 2 in part 3.4, and one band of IMF-MFs (near ELF-Mfs) may be regarded as static and can be explained through Equation 2 just like the case of ELF-MFs.…”
Section: The Hyperfine Coupling Mechanism Of Biological Effects On Anmentioning
confidence: 99%
“…Since at least the late 1950s, the public have raised the concerns about the potential biological effects of nonionizing radiation [1]. According to the European Commission, non-ionizing radiation are divided into static magnetic fields (0 Hz),extremely low-frequency (0 to 300 Hz), intermediate frequency (300 Hz to 100 kHz), and radio frequency (100 kHz to 300 GHz) fields [2].…”
Section: Introductionmentioning
confidence: 99%